2011
DOI: 10.1038/emboj.2011.398
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-based unconventional secretory pathway for extracellular delivery of IL-1β

Abstract: Autophagy controls the quality and quantity of the eukaryotic cytoplasm while performing two evolutionarily highly conserved functions: cell-autonomous provision of energy and nutrients by cytosol autodigestion during starvation, and removal of defunct organelles and large aggregates exceeding the capacity of other cellular degradative systems. In contrast to these autodigestive processes, autophagy in yeast has additional, biogenesis functions. However, no equivalent biosynthetic roles have been described for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
890
7
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 820 publications
(980 citation statements)
references
References 69 publications
48
890
7
9
Order By: Relevance
“…S1G). Our results also confirmed that the secretion of HMGB1, a previously known protein secreted through unconventional secretory pathway, 13 increased after BFA treatment, similarly to IDE (Fig. S1H).…”
Section: Ab Induces Extracellular Secretion Of Functional Ide From Assupporting
confidence: 86%
See 1 more Smart Citation
“…S1G). Our results also confirmed that the secretion of HMGB1, a previously known protein secreted through unconventional secretory pathway, 13 increased after BFA treatment, similarly to IDE (Fig. S1H).…”
Section: Ab Induces Extracellular Secretion Of Functional Ide From Assupporting
confidence: 86%
“…11 In eukaryotic cells, the autophagy-based secretory pathway (autosecretion 12 ) regulates the unconventional secretion of several cytosolic proteins such as IL1B (interleukin 1, beta), IL18, HMGB1 (high mobility group box 1), and VWF (von Willebrand factor), as well as ATP. [13][14][15] There are 3 principal features defining autophagybased secretion: 1) proteins lacking a signal sequence, 2) contribution of autophagy-related (ATG) genes, and 3) association with GORASP (Golgi reassembly and stacking protein). 16 In the brains of patients with AD and animal models, pathological autophagic vacuoles (AVs) are accumulated through increased induction via the AMPK-MTOR pathway and dysfunction in the autophagy-lysosomal degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have primarily focused on autophagy in unconventional secretion, a collection of processes through which certain proteins are secreted from cells either via direct trafficking from the endoplasmic reticulum (ER) to the plasma membrane in a Golgi-independent manner, or via the transport of cytoplasmic proteins lacking an amino-terminal ER signal sequence to the cell surface, completely bypassing the ER-Golgi route 126 . Autophagy-related proteins (ATGs) have been genetically implicated in the unconventional secretion of the acyl-CoA-binding protein Acb1 in yeast (AcbA in Dictyostelium discoideum), and inflammatory mediators such as interleukin-1β (IL-1β) and IL-18, the high mobility group protein B1 (HMGB1) and the integral membrane protein ΔF508 CFTR (cystic fibrosis transmembrane conductance regulator) in mammalian cells [127][128][129][130][131] . The unconventional secretion of these proteins is also dependent on Golgi membrane-binding proteins of the GRASP family in both yeast and mammals 129,130,132 .…”
Section: Box 2 | Autophagy and Secretionmentioning
confidence: 99%
“…FITC-conjugated CTLA-4 F(ab) 2 was used as a negative control for protein uptake ( Figure 2H). Since recent data indicate that autophagosome formation modulates IL-1β secretion [23] and many reports point to the involvement of the endolysosomal compartment in unconventional secretion [24], it is possible that CPZ affects not only endocytosis but also intracellular trafficking of endolysosomes or autophagosomes. To settle this point, we carried out experiments with two TLR agonists that do not require clathrin-mediated endocytosis, FSL-1 (TLR2 agonist), and flagellin (TLR5 agonist).…”
Section: Inhibition Of Sap Internalization and Regulation Of Il-1β Anmentioning
confidence: 99%